An interesting case of pseudoaneurysm of internal iliac artery: rare case report with review of literature - Katke, Rajshree D.; Zarariya, Ashish N.; Gutte, Avinash A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pseudoaneurysm is known to be a rare cause of secondary postpartum haemorrhage. A pseudoaneurysm is a haematoma that communicates with the lumen of a damaged parent artery via a small neck leading to turbulent flow. Herein we report a case of 32 year old multiparous patient who developed heavy vaginal bleeding 3 months post uterine curettage and was suspected to have AV malformation. Further evaluation on MRI & angiography showed small sized vaginal wall AV malformation with large pseudoaneurysm arising from within it. Its location near retropubic space in vagina, a very difficult site to approach makes this case interesting. She was treated with total abdominal hysterectomy with bilateral internal artery looping with excision of the pseudoaneurysm with successful outcome.